Prevalecencia de caries y consumo de azúcar en niños preescolares - Sánchez Montes, Juana Cruz; Reyes Murga, Ana Lourdes; Franco Marina, Francisco; Arjona Serrano, Judith; Rodríguez Vilchis, Laura (CIENCIA ergo-sum; Vol. 1 Núm. 1 (1994): CIENCIA ergo-sum (marzo-junio 1994), 2017)
-